Usability Testing Design to Increase User Experience of a Mobile Landslide Application - yanuarsyah, iksal; Ahmad, Syarbaini; Khalid, Nurkaliza (Krea-TIF: Jurnal Teknik Informatika, 2023)
The necessity of usability testing on mobile applications built for landslide disaster management is discussed in this article. The design of user usability tests is critical to ensuring that the program is effective and efficient in catastrophic conditions, and the application's success greatly depends on its usability level. This research seeks to address user needs by designing a disaster mobile application. The goal is to address comfort issues when using disaster applications and provide the necessary solutions to improve their design and functionality by establishing user usability testing. In addition to identifying and solving usability problems that may occur when using disaster mobile applications, this research intends to establish a usability testing methodology related to landslide mitigation. The method of this study starts with research design, research procedures, data collecting, and analysis within several questions that relate to respondents who live in landslide-prone areas. The aspect of the usability test was assessed, such as connectivity, awareness, familiarity, easiness, usability, functionality, accessibility, error handling, and satisfaction. Using user usability test design in disaster mobile application development can boost the app's adoption and efficacy. Users who can easily access and use the application will have better access to emergency information and support. This study concludes that designing user usability tests is a viable method for improving the usability of disaster mobile applications. The findings revealed that user performance differed by group, with rescue workers being more efficient